Evaluation of efficacy and safety of Taylor's approach for neuraxial blockade in infraumbilical surgeries with difficult lumbar access: a retrospective, single-centre study - Kulkarni, Vivek; Shah, Kshama; Tiwaskar, Shilpa; Karande, Jyotsna; Ranade, Rahul; Reddy, Priyanka; Madan, Dipti; Narechania, Vidhi; Vaze, Shweta; Gawali, Vijakumar (International Journal of Research in Medical Sciences, 2025)
Background: Spinal block, commonly known as subarachnoid anesthesia, is the most popular method for performing lower extremity procedures. In patients with difficult spinal anatomy, the Taylor modified paramedian technique has proven to be beneficial. This study aim is to assess the efficacy and safety of Taylor's technique in a heterogeneous group. Methods: This retrospective observational study was conducted from March 2018 to August 2024, involving 68 patients aged between 18 and 80 years, classified as ASA I–III. The study focused on patients with degenerative diseases or spinal anomalies that complicated lumbar puncture procedures. For regional anaesthesia, lumbar subarachnoid blocks (LSAB) were administered using Taylor's method. Data on drug dosages, complications, outcomes and procedure parameters were collected and analysed. Results: The mean time to onset of sensory and motor block was 8.26 minutes, while the mean regression time was 197.98 minutes. The procedure was successful in 97.06% of cases and a large study population needed 2–3 needle redirection attempts. Mean depth of lumbar puncture measured with Stocker's formula was 63.81 mm, which matched nearly with that of the calculated depth. Trendelenburg position was preserved for 10 minutes facilitating anaesthetic flow. The most frequent reasons for disability in the implementation of LSAB were lumbar spinal disorders 48.11% , obesity 35.85% and 16.04% had difficulty in sitting due to pain. Conclusions: The modified paramedian approach from Taylor's for LSAB is effective, rapid, and reliable technique.